Blood memory - McElroy, Colleen J. (Pitt poetry series., 2016)
Blood Memory, Colleen J. McElroy's collection of narrative poetry, emerges from deep seated memories with enormous emotion. Through the rhythms and musicality unique to McElroy's voice, it portrays an extended family, a complex culture spanning several decades, multiple victories and failures, and a single brilliant soul that frames the poems. Dedicated to McElroy's mother, the book is universal in its scope, inescapable in its earthy particularity. McElroy writes, "I am the last female of a family/ of women who wove the fabric/ of stories into doilies and slip covers.../" Blood Memory offers consummate storytelling and unforgettable poetry capturing a place and time gone forever. And as an evolving history, the poetry has a cinematic quality, large and intimate and at the same time, characters utterly vivid.